Teaching Indigenous Literatures for Decolonization: Challenging Learning, Learning to Challenge - Hanson, Aubrey Jean (Alberta Journal of Educational Research, 2020)
This paper examines the significance of colonial contexts that influence the teaching of Indigenous literatures. It draws upon conversations I held with Indigenous writers and with secondary educators, in which we discussed the relationships between Indigenous communities, Indigenous literatures, and classroom teaching in Canada. In dialogue with teachers’ and authors’ perspectives, this paper argues that, when Indigenous stories are told and taught, readers are invited to challenge colonial understandings and are implicated into challenging classroom experiences. The pedagogical experiences precipitated by Indigenous literatures can be difficult for teachers and students, leading to unsettling dynamics, but are importantly decolonizing. Keywords: Indigenous literatures, Indigenous education, decolonization, resurgence, métissage Cet article examine la signification des contextes coloniaux qui influencent l’enseignement des littératures autochtones. Il puise dans des conversations que j’ai eues avec des écrivains autochtones et des enseignants du secondaire au cours desquelles nous avons discuté des rapports entre les communautés autochtones, les littératures autochtones et l’enseignement en classe au Canada. S’appuyant sur les perspectives des enseignants et des auteurs, l’article soutient que lorsqu’on raconte ou qu’on enseigne des récits autochtones, on invite les lecteurs à remettre en question des perspectives coloniales et à participer à des expériences stimulantes en classe. Les expériences pédagogiques précipitées par les littératures autochtones peuvent s’avérer difficiles pour les enseignants et les élèves, et une dynamique perturbante peut en découler, mais leur rôle dans la décolonisation est important. Mots clés: littératures autochtones; éducation autochtone; décolonisation; résurgence; métissage